2018
DOI: 10.1136/bmjresp-2018-000320
|View full text |Cite
|
Sign up to set email alerts
|

Step oximetry test: a validation study

Abstract: IntroductionStep climbing is a potentially useful modality for testing exercise capacity. However, there are significant variations between test protocols and lack of consistent validation against gold standard cycle ergometry cardiopulmonary exercise testing (CPET). The purpose of the study was to validate a novel technique of exercise testing using a dedicated device.MethodsWe built a step oximetry device from an adapted aerobics step and pulse oximeter connected to a computer. Subjects performed lung functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…21,27 SARS-CoV-2 seems to have a viral shedding pattern similar to influenza. 34,35 High viral loads have been detected in completely asymptomatic patients, calling for a minimum level of protection from respiratory droplets for all clinicians. 30,36 SARS-CoV-2 was also noted in stool in 50% of patients tested, and extensive surface contamination has been reported.…”
Section: Personal Protective Equipment Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…21,27 SARS-CoV-2 seems to have a viral shedding pattern similar to influenza. 34,35 High viral loads have been detected in completely asymptomatic patients, calling for a minimum level of protection from respiratory droplets for all clinicians. 30,36 SARS-CoV-2 was also noted in stool in 50% of patients tested, and extensive surface contamination has been reported.…”
Section: Personal Protective Equipment Recommendationsmentioning
confidence: 99%
“…37,38 The potential for stool or fluid transmission suggest the need for concomitant contact precautions for providers within reach of a patient or contaminated surface. 30,34 The most significant controversy involving SARS-CoV-2 transmission seems to be the potential for routine airborne or aerosol spread. It is thought that the highest risk for airborne transmission occurs during aerosolizing-generating procedures, but the virus has been found to be viable in aerosols for at least 3 h. 24,34 A recent article by Santarpia et al 39 lends more support to the possibility of airborne transmission of the virus even in the absence of aerosolizinggenerating procedures.…”
Section: Personal Protective Equipment Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fox et al explored the use of oximetry along with step climbing tests in the detailed assessment of pulmonary capacity, using area under the curve of a continuous oximetry reading [33]. Whilst these authors found that oximetry thus measured correlated with severity of disease and survival, such an approach is not relevant to the remote assessment of the acutely breathless or hypoxic patient.…”
Section: Use Of Exertional Desaturation Tests In General Lung Diseasementioning
confidence: 99%